Mixed epithelial and mesenchymal metaplastic carcinoma (carcinosarcoma) of the breast: a case report - Kang, Yu (BioMed Central, 2014)
Metaplastic breast carcinoma (MBC) is an uncommon malignancy characterized by the co-existence of two or more cellular types, commonly a mixture of epithelial and mesenchymal components. A case of a female patient aged 46 years with MBC (carcinosarcoma) is presented, including mammographic, ultrasonic, gross examination, and pathological findings. After undergoing modified radical mastectomy of the left breast and subsequent six courses of adjuvant chemotherapy and endocrine therapy, the patient is now doing well with no recurrence and metastasis. Conventional treatments for invasive ductal carcinoma (IDC) may appear to be less effective. Patients with MBC would be appropriate candidates for innovative or targeted therapy regimens.